Pre-OperativeScreening for Biliary Atresia Using a Stool Color Card in Infants: In a Tertiary Care Hospital in Bangladesh - Rahman, AZM Raihanur; Mazumder, Md Wahiduzzaman; Md Rukunuzzaman; Siddique, Rasel; Mamun, Abullah Al; Haldar, Sutopa; Siddique, Shorif; Saha, Sujoy Kumar; Rahman, Md Shafiqur (Journal of Dhaka National Medical College & Hospital, 2023)
Aim of the study: To evaluate the accuracy of stool color card (SCC) for pre-operative diagnosis of biliary atresia in infants. Materials and Methods: This cross-sectional descriptive study was conducted at the Department of Pediatric Gastroenterology and Nutrition, BSMMU, Dhaka, Bangladesh. The stools of infants were compared with stool color card after collection for 3 consecutive days. Results were expressed as sensitivity, specificity, positive and negative predictive value. The study did not involve any social or legal risk to the subjects or any invasion of privacy. Results: Forty neonatal cholestasis cases were studied. Among them, 33 babies (mean age, 75.7±34.5 days) were diagnosed as biliary atresia (BA) and 7 of them (mean age, 77.1±30.5 days) as non- biliary atresia (NBA) with male predominance 24 (60%). Ultrasonography of hepatobiliary system showed non-visualized gall bladder in 8 infants in BA group. Gallbladder contraction was absent in 32 (97%) cases of BA group (P=0.01). Hepatobiliary scintigraphy showed no excretion of radiotracer in 33 (100%) infants of BA group and 6 (85.7%) infants of non-BA group (P=0.17). The relation between the SCC diagnosis and the final diagnosis of BA significant relationship (P<.05). The stool colour card showed sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of 90.9%, 77.1%, 90.9%, 77.1% and 85% respectively for the diagnosis of biliary atresia. Conclusion: Stool color card was found highly sensitive with positive predictive value along with high diagnostic accuracy. So that stool color card can be a reliable screening tool of biliary atresia. J.Dhaka National Med. Coll. Hos. 2023; 29 (02): 47-53